CHARACTERIZATION OF Corymbia citriodora WOOD FOR CONSTRUCTION - Nogueira, M. C. J. A.; Vasconcelos, J. S. [UNESP]; Araujo, V. A. de; Christoforo, A. L.; Lahr, F. A. R. (Centro Federal Educacao Tecnologica Rio Grande Norte, 2021)
The essences from sylviculture have been used for pulp and paper and charcoal industry. Hence, value-added examples for construction are essential. However, this use needs to be ensured by criteria prescribed by technical standards such as ABNT NBR 7190 (1997) used here. The present paper evaluated Corymbia citriodora wood to promote the effective construction use through the material characterization. Thus, fourteen mechanical properties and two physical properties were estimated. Changes in the property values under moisture content reduction were observed at two conditions: the initial at 30% and the standard point at 12%, according to prescriptions of this cited technical standard. In total, 2189 repeats were carried out in this document. Seven properties showed visible improvements and influences in the resistance from the observed moisture reduction: perpendicular and parallel compression values and static bending in the modulus of rupture, parallel tensile in the modulus of elasticity, and strength properties of shear stress, tangential cleavage and toughness. Mechanically, Corymbia citriodora wood can be applied efficiently for civil construction, since these results followed the trends pointed out by literature.
Keywords: Lemon; scented Gum; timber; moisture content; density; resistance